Burnout Syndrome in Nursing: factors associated with the work process (Research, Society and Development, 2020)
The aim of the present study was to analyze the factors that contributed to the development of Burnout Syndrome in the nursing team. This was a descriptive exploratory study with a quantitative approach developed in a School Hospital and in the Maternity School of a rural city in the State of Rio de Janeiro. The study sample consisted of nursing professionals (nurses and nursing technicians) with care and managerial functions in the Clinics: Medical, Surgical, Intensive Care Unit, Adult Emergency Room, Obstetrics, Gynecology and Pediatrics. The data collection period was from April to August 2019. As a data collection instrument, the instructional “Maslach Burnout Inventory (MBI)” was applied to identify the factors that contribute to the development of Burnout Syndrome in the study population and the characterization of the study clientele according to age group, sex, work sector, length of service and weekly workload. Low personal fulfillment was the result of greater representativeness in the nursing professional's speech, associated with factors of high workload performed. It is concluded that intervention strategies have to be thought about in the daily work process of this professional, directed to the environment and support the individual and collective needs of these individuals in order to promote greater shared autonomy and valorization in their work process.